The main approaches to the formation of the control action in younger schoolchildren in the process of teaching mathematics - Abdurakhmanov U.Sh. (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In this article we are talking about one of the topical issues at the same time - this is the question of the formation of control skills in the teacher as an essential component in the general context of personality formation.